Toward an Effective Legal Framework for Digital Health E-Commerce: Insights from the UAE and Indonesia - Benseghir, Mourad; Bendriss, Halima; Zerara, Aouatef; Berrahlia, Badreddine; Maamar Bentria (Lex Scientia Law Review, 2025)
This study compares the regulatory frameworks of the United Arab Emirates (UAE) and Indonesia governing the online provision and sale of health-related technologies. In technology-driven healthcare, data privacy and the security of digital transactions are central concerns. Employing a normative juridical approach, the research analyses applicable legislation, regulatory instruments, and scholarly literature in both jurisdictions. The findings indicate that the UAE has developed a relatively robust and comprehensive framework, particularly in relation to data protection and the security of digital health infrastructure, supported by detailed and stringent rules. By contrast, Indonesia’s regulatory framework remains less effective in practice, hindered by limited public awareness of data security, uneven enforcement, and implementation challenges at the local and regional levels. The study underscores the key differences between the two systems and highlights the need, especially in Indonesia, for clearer, more enforceable rules on health-related online transactions and stronger safeguards for personal health data.